DEFINING CYTOKINES CONTENTS IN SOLVING MAIN CUNICAL ISSUES - V. S. Shirinskiy; I. V. Shirinskiy (Acta Biomedica Scientifica)
Breakthroughs in cytokine biology, appraisal of their importance in many diseases, and successes of anticytokine therapy have lead to an assumption that cytokines can be used as biomarkers in various clinical settings. The aim of this review is to discuss some data from the literature and our own data pertaining to the use of cytokines as biomarkers for the assessment of disease burden, prognosis, diagnosis, and prediction of response to treatment.